PENGARUH MEDIA LEAFLET TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG BAHAYA ROKOK DI MTSS DDI CAMBALAGI KABUPATEN MAROS - Rismalasari Syam Rismalasari; Muhammad Syafar Syafar; Muhammad Rifai Rifai (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2022)
Smoking is an unhealthy behavior that causes various diseases, ironically this smoking habit, especially in Indonesia, seems to have been entrenched even though many smokers are actually aware and admit that smoking will cause various kinds of diseases in their bodies.The purpose of the study: to determine the effect of leaflet media on the knowledge and attitudes of adolescents about the dangers of smoking at MTS DDI Cambalagi, Maros Regency in 2021. Type of Research: The research design used is Pre Experiment Designs with the one group Pretest-Posttest Design method. The sample in this study were 38 respondents. Simple random sampling technique.The results of the study: The knowledge of students before being given leaflets about the dangers of smoking from 38 respondents who had good knowledge as many as 4 respondents (10.5%) enough as many as 8 respondents (21.1%) less as many as 26 respondents (68.4%) after being given the media experienced an increase in good knowledge as many as 18 respondents (47.4%) enough as many as 16 respondents (42.1%) less as many as 4 respondents (42.1%) decreased, while the attitude of students before being given leaflets about the dangers of smoking were positive as many as 7 respondents (18.4%) negative as many as 31 respondents (81.6 %), after being given leaflet media, there was an increase in the positive attitude of 26 respondents (68.4%) who had a negative attitude decreased by 12 respondents (31.6%). The results of the Wilcoxon test showed that there was an effect of student knowledge before and after being given leaflet media about the dangers of smoking with a value (p = 0.000), There was an influence on student attitudes before and after being given leaflet media about the dangers of smoking with a value (p = 0.000). Suggestion: For teachers and students, it is hoped that this research can be used as information material for teachers and students in order to know about the dangers of smoking and the diseases that can be caused by smoking through the provision and installation of leaflet on the dangers of smoking in the school environment, as well as providing always explain about the dangers of smoking. Keywords : Leaflet, knowledge, attitude, cigarettes